PROBLEMS OF ADVANCED TECHNOLOGIES IMPLEMENTATION IN THE ROAD CONSTRUCTION - Т. Shemyakina; K. Barkaev (Вестник университета, 2019)
In article the strategy of transport system development and a role of road construction in development of infrastructure, the management concept, a role of a technological transfer in implementation of technologies, the directions of perspective technologies, organizational process of technology transfer from the point of view of functioning of innovative system and forming business processes in the construction organization are considered.